THE SURVIVAL OF GORAN IDENTITY IN KOSOVO AND METOHIJA: THE ROLE OF THE REPUBLIC OF SERBIA AND THE BRUSSELS PROCESS - Semenov, Andrej; Nedeljković, Zoran (National interest, 2025)
The paper aimed to explain the concept of “nuclear sharing” in Europe and determine the direction of its further development, such as proliferation, control, or elimination. It used historical and content analysis, synthesis, and comparative approaches. Historical analysis showed the fundamental motives for the emergence of the US “nuclear sharing,” its inextricable link with the expanded deterrence and defense of the US, and its role in NATO. As an instrument of non-proliferation in Europe, “nuclear sharing” was supposed to provide sufficient security guarantees to the US allies so that they would not choose the path of creating their nuclear weapons or cooperating with the already existing European atomic weapons. The Federal Republic of Germany issue was of special concern to both the US and USSR. The “nuclear sharing” was supposed to enable both a stronger binding of the allies to the US and the creation of transatlantic unity, but also to maintain the European balance of power between states that possess and those that do not have nuclear weapons. In addition, the new roles of “nuclear sharing” cannot be linked only to the relationship with Russia but also to the emergence of new threats, especially those in the Middle East, as perceived by the US and its NATO allies. The paper then discussed the controversies of “nuclear sharing” that were known during the negotiations of the Non-Proliferation Treaty, but which, with the end of the Cold War, became questionable again, not only for Russia but especially for other NPT member states. These controversies relate to Articles 1 and 2 of the NPT (interpretation of the term "transfer" of nuclear weapons), whether it also limits the deployment of delivery systems, the obligation to move towards nuclear disarmament under Article 6 of the NPT, the invalidity of the Treaty in the event of war, as well as the training of the armed forces of non-nuclear-weapon states under the NPT for the performance of nuclear missions and the use of nuclear weapons. In terms of effectiveness, the paper examined the controversies of suitability of “nuclear weapons” for deterrence and defense against asymmetric threats, the need for their continued retention if the strategic forces of NATO members are sufficient for the role of deterrence and defense of the entire NATO, the credibility of American guarantees of extended deterrence, the suitability of the deployed tactical nuclear weapons for nuclear deterrence and defense in Europe, and the effectiveness of the air component of nuclear deterrence and defense, i.e. the limitations on the ability of dual-capability aircraft to deliver nuclear weapons to targets. Finally, the paper considered the future of the development of “nuclear sharing,” considering previous historical analysis and controversies. Three possible directions for the development of “nuclear sharing” are considered – proliferation (horizontal, vertical, and the possibility of “succession” of the nuclear status of the European Union from France), control, and elimination of “nuclear sharing” in Europe. The trend that tends to prevail in the conditions of the wars in Ukraine and the Middle East is proliferation from both the Russian and American sides. Although the status of “nuclear sharing” within the West remains unchanged, the pressure from Eastern European allies is growing stronger, especially from more conservative parties. On the other side, developing European nuclear deterrence by giving a “European dimension” to French atomic deterrence would raise the question of relations with the US – competitiveness or complementarity. The “nuclear sharing” issue with Turkey has been identified as the most controversial since ties with the US have weakened, those with Russia have strengthened, and the Turkish defense industry has established a more independent development. As for the elimination of “nuclear sharing,” the paper examined the options of the allies concerned own demands to end the sharing and the possibility of accession to the Treaty on the Prohibition of Nuclear Weapons.
Keywords: Gorani; Gorani community; Belgrade-Pristina Dialogue; Brussels Agreement; Ohrid Agreement; German- French proposal; Serbia; Kosovo and Metohija; European Union